The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3839/jabc.2013.030
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Emodin Isolated from Cassia tora Linn. Seeds against Food-Borne Bacteria

Abstract: The antimicrobial activities of emodin and its derivatives (anthraquinone, alizarin, and alizarin-3-methyliminodiacetic acid) were evaluated using a paper disc diffusion method against foodborne bacteria (Bacillus cereus, Listeria monocytogenes, Staphylococcus intermedius, Salmonella typhimurium and Shigella sonnei). Emodin isolated from C. tora seeds has an antimicrobial activity against Bacillus cereus, followed by alizarin-3-methyliminodiacetic acid (13.0±2.5 mm) and alizarin (11.5±1.2 mm). Furthermore, emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Phytochemicals may exhibit different modes of action against enterotoxigenic bacterial strains which range from interference with the phospholipoidal cell membranes, which has as a consequence of increasing the permeability profile and loss of cellular constituents, damage of the enzymes involved in the production of cellular energy and synthesis of structural components, and destruction or inactivation of genetic material [ 16 ]. The antimicrobial activities of emodin isolated from C. tora and its derivatives (anthraquinone, alizarin, and alizarin-3-methyliminodiacetic acid) against foodborne bacteria ( Bacillus cereus, Listeria monocytogenes, Staphylococcus intermedius, Salmonella typhimurium , and Shigella sonnei ) were described [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals may exhibit different modes of action against enterotoxigenic bacterial strains which range from interference with the phospholipoidal cell membranes, which has as a consequence of increasing the permeability profile and loss of cellular constituents, damage of the enzymes involved in the production of cellular energy and synthesis of structural components, and destruction or inactivation of genetic material [ 16 ]. The antimicrobial activities of emodin isolated from C. tora and its derivatives (anthraquinone, alizarin, and alizarin-3-methyliminodiacetic acid) against foodborne bacteria ( Bacillus cereus, Listeria monocytogenes, Staphylococcus intermedius, Salmonella typhimurium , and Shigella sonnei ) were described [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…19,31 Moreover, emodin (2) possesses multiple pharmacological functions and has been widely used in the treatment of cancer, asthma, atherosclerosis, osteoarthritis, diabetes, Alzheimer's disease (AD), and hepatic disease. 19,29,30,32,33 In this study, emodin (2) displayed some antifungal activity against 6 plant pathogenic fungi, showing highest activity toward the pathogenic fungi B. maydis. The results of the mechanism of emodin (2) on the pathogen revealed that emodin (2) could affect the colony morphology, destroy cell membrane integrity and influence protein synthesis of the tested fungal cell.…”
mentioning
confidence: 70%
“…Kaempferol and luteolin have also been isolated from C. alata and C. fistula and displayed a strong DPPH scavenging activity [ 28 , 29 , 30 ]. On the other hand, anthraquinones were found as the major phenolic compounds present in Cassia species [ 31 ], while emodin, aloe-emodin, rhein, and chrysophanol are widely distributed in Cassia species such as C. tora [ 32 ], C. roxburghii [ 33 ], C. alata [ 34 , 35 ], C. obtuse [ 36 ], C. siamea [ 37 ], and C. angustifolia [ 38 ]. All of these previous findings are in good agreement with our present study that demonstrates C. timoriensis extract to possess high contents of flavonoids and phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%